Implementation of Health Belief Models (HBM) Education for Tuberculosis patients at the Tamansari Primary Health Care, Tasikmalaya City - Lilis Lismayanti; Miftahul Falah; Ijang Budiana; Angga Riadi Permana; Deba Yasa Zakia; Moh. Alvin Aditia; Rosmiati Rosmiati (ABDIMAS: Jurnal Pengabdian Masyarakat, 2021)
Tuberculosis (TB) is an infectious disease that continues to increase not only nationally but also globally. Tuberculosis is a problem for sufferers both physically and psychologically, it can even cause negative stigma from themselves and society, so the disease affects the quality of life of the sufferer. Tuberculosis treatment that is long enough and requires compliance can cause susceptible to drop out (DO), finally will increase the risk of cases of Multi Drug Resistance (MDR). The role of nurses is needed in ensuring tuberculosis patient adherence in treatment. Patient will be understand that tuberculosis is important in the treatment process. Education is a strategy in increasing patient understanding to change positive behavior for tuberculosis sufferers. The aim of this community service is to implement Health Belief Models (HBM) Education in Tuberculosis patients. This method used lectures, interviews and practice. The results found that the implementation of HBM on 19 patients who visited Tamansari primary health care for 3 months showed a significant result in behavior and quality of life. HBM education can change the quality of life of tuberculosis sufferers by changing perceptions of the disease which includes perceptions of vulnerability, perception of severity, perceived benefits, perceptions of barriers and a person's belief in healthy behavior. It is recommended that HBM education should continue to be implemented for tuberculosis sufferers so that they can maintain their survival.